Determining the relationship between hormonal background characteristics and signs of female sexual dysfunction in women with and without endometriosis in the prediction of gestational success - L.M. Semeniuk; V.I. Pankiv; Ye.S. Kozachuk; O.I. Kryzhanovska (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Overcoming infertility in young women is recognized as one of the most important tasks of modern medicine. Among the factors that reduce female fertility, endometriosis remains relevant. The widespread prevalence of diseases with common pathogenetic factors has led to the emergence of diseases of “old age” in women of reproductive age. These include, in particular, female sexual dysfunction (FSD). The relationship between FSD and hormonal indicators as prognostic factors of female reproductive health has been little studied to date. The purpose was to determine the relationship between the characteristics of the hormonal background and signs of FSD in women with and without endometriosis in the prediction of the success of future gestation. Materials and methods. The study design is a prospective cohort study, which included 130 women of reproductive age. They were divided into 3 groups: group IA (n = 70) — a combination of female sexual dysfunction and extragenital endometriosis, the comparison group IB (n = 30) — female sexual dysfunction without extragenital endometriosis, the control group II (n = 30) — healthy reproductively active women. The end points of the study were levels of pituitary and ovarian hormones, proandrogenic steroids, ovulatory menstrual cycles. These indicators were studied before treatment and at the control periods of therapy — 3, 6, 9 months. The presence of FSD was determined using a questionnaire with scoring on an online calculator, when the female sexual function index was less than 26.55 points. The therapy was aimed at restoring the correct functioning of ovarian steroidogenesis using herbal therapy. Statistical analysis was performed using a specialized statistical software package SPSS 25.0 (StatSoft Inc., USA). Results. A significant normalization of pituitary peptide hormones in the comparison groups occurred in the period from the sixth to the ninth month of therapy. As for the estradiol level, its significant increase was noted in both comparison groups throughout the entire observation period. At the ninth month, the values of progesterone in patients with FSD and endometriosis were significantly higher in than those without it (p = 0.002). Despite the treatment, the estradiol and progesterone levels in the IA group remained significantly lower than in the control group throughout the entire observation period (p < 0.001). In patients without endometriosis (IB group), after 9 months of treatment, only estrogen values were successfully corrected, which were comparable to the control group. Analysis using Dunn’s test with Bonferroni correction showed no statistically significant difference between the IA and IV groups throughout the entire course of treatment (p > 0.05). Correlation analysis revealed that in patients with FSD and endometriosis after 6 months of treatment, changes in the studied hormones statistically significantly correlated with improvements in scores in all domains of the questionnaire. At the control period of 6 months, 20 (66.3 %) women were not ready for safe conception. In the 9-month control period, 16 (53.3 %) patients in this group were not ready for safe motherhood. Conclusions. Women with external-internal endometriosis and FSD and women with FSD alone have different pathogenetic background in the formation of gestational pathology. Therapy of patients with any form of FSD should be personalized. Assessment of FSD domains allows for rapid diagnosis of future gestational risks in women of reproductive age.